Interactions Between Clostridioides difficile and Fecal Microbiota in in Vitro Batch Model: Growth, Sporulation, and Microbiota Changes - Horvat, Sabina; Rupnik, Maja (Frontiers in Microbiology, 2018)
Disturbance in gut microbiota is crucial for the development of Clostridioides difficile infection (CDI). Different mechanisms through which gut microbiota influences C. difficile colonization are known. However, C. difficile could also affect gut microbiota balance as previously demonstrated by cultivation of fecal microbiota in C. difficile conditioned medium. In current study the interactions of C. difficile cells with gut microbiota were addressed. Three diferent strains (ribotypes 027, 014/020 and 010) were co-cultivated with two types of fecal microbiota (healthy and dysbiotic) using in vitro batch model. While all strains showed higher sporulation frequency in the presence of dysbiotic fecal microbiota, the growth was strain dependent. C. difficile either proliferated to comparable levels in the presence of dysbiotic and healthy fecal microbiota or grew better in co-culture with dysbiotic microbiota. In co-cultures with any C. difficile strain fecal microbiota showed decreased richness and diversity. Dysbiotic fecal microbiota was more affected after co-culture with C. difficile than healthy microbiota. Altogether, 62 OTUs were significantly changed in co-cultures of dysbiotic microbiota/C. difficile and 45 OTUs in co-cultures of healthy microbiota/C. difficile. However, the majority of significantly changed OTUs in both types of microbiota belonged to the phylum Firmicutes with Lachnospiraceae and Ruminococcaceae origin.